Step * 1 2 1 1 1 of Lemma rlog-rmul


1. : ℝ
2. r0 < x
3. : ℝ
4. r0 < y
5. r0 < (x y)
6. λx.(rlog(x y) rlog(y)) ∈ (r0, ∞) ⟶ℝ
7. : ℝ
8. ∀x:{x:ℝx ∈ (r0, ∞)} (rlog(x) ((rlog(x y) rlog(y)) c))
9. r0 c
10. rlog(x) ((rlog(x y) rlog(y)) c)
11. r0 < (r1 y)
⊢ rlog(x y) (rlog(x) rlog(y))
BY
(RWO "-3<(-2) THENA Auto) }

1
1. : ℝ
2. r0 < x
3. : ℝ
4. r0 < y
5. r0 < (x y)
6. λx.(rlog(x y) rlog(y)) ∈ (r0, ∞) ⟶ℝ
7. : ℝ
8. ∀x:{x:ℝx ∈ (r0, ∞)} (rlog(x) ((rlog(x y) rlog(y)) c))
9. r0 c
10. rlog(x) ((rlog(x y) rlog(y)) r0)
11. r0 < (r1 y)
⊢ rlog(x y) (rlog(x) rlog(y))


Latex:


Latex:

1.  x  :  \mBbbR{}
2.  r0  <  x
3.  y  :  \mBbbR{}
4.  r0  <  y
5.  r0  <  (x  *  y)
6.  \mlambda{}x.(rlog(x  *  y)  -  rlog(y))  \mmember{}  (r0,  \minfty{})  {}\mrightarrow{}\mBbbR{}
7.  c  :  \mBbbR{}
8.  \mforall{}x:\{x:\mBbbR{}|  x  \mmember{}  (r0,  \minfty{})\}  .  (rlog(x)  =  ((rlog(x  *  y)  -  rlog(y))  +  c))
9.  r0  =  c
10.  rlog(x)  =  ((rlog(x  *  y)  -  rlog(y))  +  c)
11.  r0  <  (r1  *  y)
\mvdash{}  rlog(x  *  y)  =  (rlog(x)  +  rlog(y))


By


Latex:
(RWO  "-3<"  (-2)  THENA  Auto)




Home Index